1991
DOI: 10.1002/ajmg.1320400118
|View full text |Cite
|
Sign up to set email alerts
|

Newly recognized syndrome of cerebral, ocular, dental, auricular, skeletal anomalies: CODAS syndrome—a case report

Abstract: We report on a child with a unique constellation of congenital anomalies suggesting a new syndrome. These consist of developmental delay; craniofacial abnormalities, including bilateral cataracts, ptosis, median nasal groove, malformed ears with associated neurosensory hearing loss; dental anomalies consisting of anomalous cusp morphology with unusual pointed extensions and delayed tooth eruption; short stature with marked delay in epiphyseal ossification; coronal clefts involving vertebrae T11-S2; and disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Nevertheless, this child is the second affected child of Mennonite ancestry living in the Canadian province of Manitoba. The ®rst child described has unfortunately been lost to follow-up [Shebib et al, 1991]. The Old Colony Mennonites have previously been recognized as`a genetic and religious isolate with a distinct pattern of inherited disease'' [Jaworski et al, 1989].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this child is the second affected child of Mennonite ancestry living in the Canadian province of Manitoba. The ®rst child described has unfortunately been lost to follow-up [Shebib et al, 1991]. The Old Colony Mennonites have previously been recognized as`a genetic and religious isolate with a distinct pattern of inherited disease'' [Jaworski et al, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…It would appear to be rare, as only two cases have been reported in the literature [Shebib et al, 1991;Cabral de Almeida et al, 1995]. The phenotype appears to be remarkably distinctive, with typical facial features, developmental delay, congenital cataracts, unusual dental ®ndings, and skeletal anomalies.…”
Section: Introductionmentioning
confidence: 96%
“…Two unrelated Manitoba Mennonite children were described with multiple anomalies consisting of cerebral, ocular, dental, auricular, and skeletal abnormalities and designated by the acronym CODAS syndrome [Shebib et al, 1991;Innes et al, 2001]. The authors suggested the possibility of autosomal recessive inheritance in this disorder; however, there had not been a familial recurrence to the time of this study.…”
Section: Presumed Autosomal Recessivementioning
confidence: 92%
“…Cerebral, ocular, dental, auricular, skeletal anomalies (CODAS) syndrome is a rare, multi-system developmental disorder originally described in 1991 [65]. Less than 20 cases have been reported to this day [6567].…”
Section: Lon Involvement In Human Diseasesmentioning
confidence: 99%
“…Less than 20 cases have been reported to this day [6567]. Two different groups reported in 2015 that the genetic abnormalities causing the CODAS Syndrome are compound heterozygous or homozygous mutations in LONP1 (either missense or nonsense point mutations or small in-frame deletions) [66,67].…”
Section: Lon Involvement In Human Diseasesmentioning
confidence: 99%